A study of diurnal and short-term variations of indoor radon concentrations at the University of Michigan, USA and their correlations with environmental factors. Issue 8 (October 2017) - Xie, Dong; Liao, Maili; Wang, Hanqing; Kearfott, Kimberlee J.
Measurements of indoor radon concentrations and environmental parameters were collected continuously on an hourly basis over a three-month period (April 2012 to June 2012). These were performed both in a well-ventilated ground floor laboratory and in the unventilated basement directly below it in a two-storey building at the University of Michigan, USA. The diurnal variations of indoor radon concentration were investigated along with their correlations to the environmental parameters. The results showed that in the laboratory with typical air exchange, the highest radon values appeared in the early morning while lower values emerged in the afternoon. A similar time-course was followed by radon concentrations in the basement with stagnant air. The day-average radon concentrations in the laboratory ranged from 27 ± 2 Bq m −3 to 54 ± 5 Bq m −3, with the overall mean of 37 ± 6 Bq m −3 over the three-month data collection period. The overall basement average, 900 ± 92 Bq m −3 is significantly higher than the population-weighted world average value of 39 Bq m −3 . For the ground-level laboratory, the indoor humidity, outdoor temperature and indoor–outdoor temperature difference were positively correlated with indoor radon. The indoor radon negatively correlated with outdoor barometric pressure, wind speed and indoor–outdoor barometric pressure differences. However, for the unventilated basement, the only statistically significant correlation of indoor radon concentration was a positive one with hourly rainfall.